Capacity planning in textile and apparel supply chains. (26th April 2018) - Safra, Imen; Jebali, Aida; Jemai, Zied; Bouchriha, Hanen; Ghaffari, Asma
Abstract: This study deals with production and distribution planning for a textile and apparel supply chain. Given the seasonal nature of demand, global character of the textile and apparel supply chain, short life cycle of apparel products and demand unpredictability of trendy items, manufacturers require an efficient and flexible planning system that incorporates in-season replenishment orders with short lead time and preseason orders with medium lead time. A planning approach integrating tactical and operational decisions is proposed. Using a rolling horizon, the proposed approach determines the quantities to produce, store and deliver, which minimize the total production and distribution cost. At the tactical planning level, a percentage of production capacity is reserved in order to accommodate replenishment orders that are difficult to predict. Moreover, production of standardized items with predictable demand could be assigned to overseas low-cost subcontractors. For operational planning, local subcontracting and overtime could be used as options to address the unpredictability of the demand tied to replenishment orders. Our results show that the proposed approach results in a 10% cost saving over current practice.